Two new pathotypes-29R45 and 93R39 of Puccinia triticina from India - I.K. KALAPPANAVAR, S.C. BHARDWAJ*, M. PRASHAR, SUBODH KUMAR S.K. JAIN, D. DATTA and (Indian Phytopathology, 2006)
Two new pathotypes 29R45 and 93R39 of Puccinia triticina Eriks. (Brown rust of wheat) are described here. Both the pathotypes are virulent on Lr26 (1BL.1RS translocation), which occurs in about 40% of the recently identified Indian wheat varieties. Pathotypes 29R45 is virulent on Lr23 whereas 93R39 is avirulent. In addition to virulence on bread wheat, pathotype 29R45 was found more virulent on durum, emmer wheat and some barley lines. Implications of new pathotypes, their avirulence/virulence formulae, and resistance sources are listed.